Preparation, features, and efficiency of nanocomposite fertilisers based on glauconite and ammonium dihydrogen phosphate - Rudmin, Maxim; Makarov, Boris; López-Quirós, Adrián; Maximov, Prokopiy; Lokteva, Valeria; Ibraeva, Kanipa; Kurovsky, Alexander V.; Gummer, Yana; Ruban, Alexey (Materials)
This paper studies the chemical and mechanochemical preparation of glauconite with ammonium dihydrogen phosphate (ADP) nanocomposites with a ratio of 9:1 in the vol.% and wt.%, respectively. The methods include X-ray diffraction analysis, scanning electron microscope with energy-dispersive X-ray spectroscopy, transmission electron microscopy, infrared spectroscopy, and differential thermal analysis with a quadruple mass spectrometer. The manufactured nanocomposites keep the flaky glauconite structure. Some glauconite unit structures have been thickened due to minimal nitrogen (ammonium) intercalation into the interlayer space. The globular, granular, or pellet mineral particles of nanocomposites can be preserved via chemical techniques. Globular and micro-aggregate particles in nanocomposites comprise a thin film of adsorbed ADP. The two-step mechanochemical method makes it possible to slightly increase the proportion of adsorbed (up to 3.2%) and intercalated (up to 6.0%) nutrients versus chemical ways. Nanocomposites prepared via chemical methods consist of glauconite (90%), adsorbed (1.8–3.6%), and intercalated (3.0–3.7%) substances of ADP. Through the use of a potassium-containing clay mineral as an inhibitor, nitrogen, phosphorus, and potassium (NPK), nanocomposite fertilisers of controlled action were obtained. Targeted and controlled release of nutrients such as phosphate, ammonium, and potassium are expected due to various forms of nutrients on the surface, in the micropores, and in the interlayer space of glauconite. This is confirmed via the stepwise dynamics of the release of ammonium, nitrate, potassium, and phosphate from their created nanocomposites. These features of nanocomposites contribute to the stimulation of plant growth and development when fertilisers are applied to the soil